Al-Simā ‘Inda Sībawaih fī Ushul An-Nahwi - Ika Mahmudah Fauziah; Maman Abdurrahman; Asep Sopian (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2021)
Al-sima 'is one of the main pillars in the construction of the theory of Arabic grammar, and it is the main step in laying the foundations and pillars of the theory. Hearing is not an easy process because it is a group of actions that begin with reflections and end with revealing of the rules, and between beginning and ending classification, division and extrapolation. The hearing does not stop within the limits of deduction, but rather other burdens are assigned to it, and it is not difficult to determine the tasks assigned to it. The measurement becomes a method of inference in the later stages, such as measurement, cause, walking, division and inference in the first, and these methods are used to achieve grammatical rules or deny the phenomenon. When Sibawayh was a master in grammar, even his companions excelled in it, so the scholars of Basra celebrated him, whose clouds were not defensible, and he brought out to people writing what he earned, and Sibawayh was the pride of eternity because he was a true witness at the height of Sibawayh in this art and grammatical sciences.